Analysis of The Employee Compensation System at The Plaza Inn Hotel Kendari City - Yuana, Indira; Hamida, La Ode; Paluala, Kusman; Syamad, Abdul; Ramadhani, Dwi Tasya (Journal of International Conference Proceedings, 2024)
This study aims to analyze the employee compensation system implemented at the Plaza Inn Hotel Kendari City. The research employs a qualitative descriptive method emphasizing Simamora’s compensation concept, which consists of four main indicators: wages or salaries, incentives, benefits, and facilities. Data were collected through documentation, interviews, and observation, using purposive sampling to select relevant informants. The findings reveal that the compensation system at the Plaza Inn Hotel Kendari City is generally well implemented. Wages and salaries are provided according to a time-based system and meet or exceed the regional minimum wage standards. Incentives are distributed fairly based on performance results, aligning with employees’ duties and responsibilities. Allowances are considered sufficient and are provided in line with employees’ needs. Moreover, the facilities offered are highly supportive of employees’ work performance, ensuring comfort and productivity. Overall, the study concludes that the compensation system at Plaza Inn Hotel Kendari City effectively supports employee satisfaction and motivation, thereby contributing to improved organizational performance